2004
DOI: 10.1038/sj.onc.1208260
|View full text |Cite
|
Sign up to set email alerts
|

A network of clinically and functionally relevant genes is involved in the reversion of the tumorigenic phenotype of MDA-MB-231 breast cancer cells after transfer of human chromosome 8

Abstract: Several investigations have supposed that tumor suppressor genes might be located on human chromosome 8. We used microcell-mediated transfer of chromosome 8 into MDA-MB-231 breast cancer cells and generated independent hybrids with strongly reduced tumorigenic potential. Loss of the transferred chromosome results in reappearance of the malignant phenotype. Expression analysis identified a set of 109 genes (CT8-ps) differentially expressed in microcell hybrids as compared to the tumorigenic MDA-MB-231 and rerev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…An approach to identify differentially expressed genes associated with molecular pathways relevant in carcinogenesis is to integrate expression results generated by the comparative analysis of cancer samples, with those generated in manipulated cancer cell line models in which tumorigenicity has been affected. In a recent study of tumor suppression due to microcell mediated transfer of chromosome 8 into a breast cancer cell line, the transcriptome analysis of the resulting hybrids identified genes that were also transcriptionally modified in human breast tumors 23. Similar studies have been conducted with chromosome 17 transfer in another breast cancer cell line 24 and transfer of chromosome 11 into an ovarian cancer cell line 25, where selected genes that were altered by chromosome transfer, were also altered in tumor samples.…”
Section: Introductionmentioning
confidence: 78%
“…An approach to identify differentially expressed genes associated with molecular pathways relevant in carcinogenesis is to integrate expression results generated by the comparative analysis of cancer samples, with those generated in manipulated cancer cell line models in which tumorigenicity has been affected. In a recent study of tumor suppression due to microcell mediated transfer of chromosome 8 into a breast cancer cell line, the transcriptome analysis of the resulting hybrids identified genes that were also transcriptionally modified in human breast tumors 23. Similar studies have been conducted with chromosome 17 transfer in another breast cancer cell line 24 and transfer of chromosome 11 into an ovarian cancer cell line 25, where selected genes that were altered by chromosome transfer, were also altered in tumor samples.…”
Section: Introductionmentioning
confidence: 78%
“…Excitingly, potential tumour suppressor genes for ovarian cancer have been found on chromosome 22 (22q11-q12) (Kruzelock et al 2000), chromosome 3 (Rimessi et al 1994), chromosome 6 (6q27) (Acquati et al 2001) and chromosome 11 (Cao et al 2001), the latter study has led to the proposition of THY1 being a tumour suppressor gene for ovarian cancer (Abeysinghe et al 2003(Abeysinghe et al , 2004. Further, genes contained on chromosome 6 (Negrini et al 1994) and the short arm of chromosome 8 have been shown, by MMCT studies, to be important in breast cancer (Wilson et al 2003;Seitz et al 2005) and colorectal cancer (Flanagan et al 2004). Indeed, it is now evident that a network of genes all found on chromosome 8 are important for the control of tumourigenicity in breast cancer cells (Seitz et al 2005).…”
Section: Biological Uses Of Mmctmentioning
confidence: 94%
“…Further, genes contained on chromosome 6 (Negrini et al 1994) and the short arm of chromosome 8 have been shown, by MMCT studies, to be important in breast cancer (Wilson et al 2003;Seitz et al 2005) and colorectal cancer (Flanagan et al 2004). Indeed, it is now evident that a network of genes all found on chromosome 8 are important for the control of tumourigenicity in breast cancer cells (Seitz et al 2005). Chromosome 8 also contains genes that reverse cancerous phenotype in rat prostate cancer cells (Nihei et al 1996(Nihei et al , 2002 as does chromosome 20 (20p11.23-12) (Goodarzi et al 2001).…”
Section: Biological Uses Of Mmctmentioning
confidence: 96%
“…The preparation of tissue sample cRNA was as previously described (Seitz et al, 2005). The study was performed with the approval of the local ethics committees.…”
Section: Microarray Sample Preparation and Experimentsmentioning
confidence: 99%